Analisis Perbandingan Biaya dan Waktu Pekerjaan Precast Beton Hexagonal Dengan Bahan Timbunan di Container Yard Banjarmasin (Magister Teknik Sipil, Fakultas Teknik, Universitas 17 Agustus 1945 Surabaya, 2023)
Trisakti Terminal, Port of Banjarmasin Branch, South Kalimantan is a busy terminal among the ten other terminals managed by PT. Pelabuhan Indonesia III (Persero) Kalimantan Regional which serves general cargo and dry bulk goods both domestically and internationally. The planning of road surface elevation and container yards depends on the type of soil and the type of structure to be built on it. So that the type of construction to be built must be adapted to the conditions and properties of the soil. The purpose of this study is to compare the construction of hexagonal precast concrete with embankment materials 1). In order to find out the comparison of construction costs to get efficient, 2). In order to know the comparison of faster implementation time, 3). In order to find out the type of construction on the strength of the structure based on applicable regulations, the research method used in the structural analysis of SAP 2000 version 14 for the analysis of hexagonal precast concrete structures while for the analysis of the embankment material structure uses the regulations of the Directorate General of Highways, Department of Public Works 1992 and to find out costs construction and time are used for unit price analysis by calculating the production capacity of hexagonal precast concrete construction and backfill materials, the results of the analysis are made in a ratio of 1). Construction cost per m², 2). Time ratio for carrying out special work on road surface elevation and container yards. After the analysis was carried out, the results showed that 1). The cost of hexagonal precast construction is 9% more efficient than embankment construction, 2), Hexagonal precast concrete construction is 12% faster than embankment construction.